2003
DOI: 10.1021/bi035119+
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Docking Loops of the cPLA2 C2 Domain:  Detailed Structural Analysis of the Protein−Membrane Interface via Site-Directed Spin-Labeling

Abstract: C2 domains are protein modules found in numerous eukaryotic signaling proteins, where their function is to target the protein to cell membranes in response to a Ca 2+ signal. Currently, the structure of the interface formed between the protein and the phospholipid bilayer is inaccessible to high-resolution structure determination, but EPR site-directed spin-labeling can provide a detailed medium-resolution view of this interface. To apply this approach to the C2 domain of cytosolic phospholipase A 2 (cPLA 2 ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
130
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(151 citation statements)
references
References 61 publications
21
130
0
Order By: Relevance
“…Our earlier study demonstrated that the effects of C1P binding are more prominent on the isolated C2 domain than full-length cPLA 2 ␣, suggesting that C1P effects are more local to the C2 domain binding of cPLA 2 ␣. The current study opens an avenue to investigate the nature and orientation of cPLA 2 ␣ as well as its isolated C2 domain at the C1P-and PtdIns(4,5)P 2 -containing membrane interface through lipid penetration analysis (10), EPR (37,41,42), x-ray reflectivity studies (38), or molecular dynamics simulations (41).…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier study demonstrated that the effects of C1P binding are more prominent on the isolated C2 domain than full-length cPLA 2 ␣, suggesting that C1P effects are more local to the C2 domain binding of cPLA 2 ␣. The current study opens an avenue to investigate the nature and orientation of cPLA 2 ␣ as well as its isolated C2 domain at the C1P-and PtdIns(4,5)P 2 -containing membrane interface through lipid penetration analysis (10), EPR (37,41,42), x-ray reflectivity studies (38), or molecular dynamics simulations (41).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, R1 side chains on the surface of bacteriorhodopsin, facing the headgroups of the bilayer, have intermediate mobility (15) much higher than that observed for 144R1 on annexin B12 bound to bilayers. Relevant to the present work are SDSL studies of the Ca 2ϩ -dependent binding to phospholipid bilayers of the C2 domains of phospholipase A 2 (27) and protein kinase C (28) to phospholipid bilayers. In these studies, R1 was placed at sites within the Ca 2ϩ -binding loops of these proteins, and some of these sites localized to the headgroup region of the bilayer in the bound state.…”
Section: Discussionmentioning
confidence: 99%
“…The Ca 2+ dependence of the fluorescence increase was quantified by plotting the fluorescence change (ΔF) as a function of free Ca 2+ concentration ([Ca 2+ ]) and best-fitted using a Hill equation (18): (1) where ΔF max represents the calculated maximal fluorescence change (normalized to 1.0 to facilitate comparison of different mutant samples), H represents the Hill coefficient, and [Ca 2+ ] 1/2 represents the free Ca 2+ concentration that induces half-maximal fluorescence change. Best-fitting was carried out via nonlinear least-squares analysis in Kaleidagraph 3.5 (Synergy).…”
Section: Fluorescence Measurement Of Ca 2+ Bindingmentioning
confidence: 99%